2017
DOI: 10.3892/mco.2017.1432
|View full text |Cite
|
Sign up to set email alerts
|

MHC class II associated stomach cancer mutations correlate with lack of subsequent tumor development

Abstract: Abstract. The role of tumor cell expression of major histocompatibility class II (MHCII) has been controversial, with evidence indicating that tumor cell expression of MHCII may lead to an anti-tumor immune response and to tumor cell apoptosis and that MHCII has pro-tumorigenic functions. The cancer genome atlas (TCGA) indicates numerous deleterious mutations for the highly specific, MHCII transcriptional activation proteins, RFX5, RFXAP, RFXANK and CIITA. Also, mutations in the non-polymorphic, human leukocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 20 publications
(15 reference statements)
0
9
0
Order By: Relevance
“…The expression of these molecules in tumor cells may play different roles in the biological behavior of tumors, sometimes triggering an antitumor immune response, leading to apoptosis of neoplastic cells, or eliciting protumoral functions, favoring tumor growth. 11,[22][23][24] The present study demonstrated for the first time a higher HLA-DR expression in LLSCC tumor cells when compared to cases of AC, suggesting a potential Unlike MHC-I molecules, which are expressed in all nucleated cells, the expression of MHC-II proteins is physiologically observed only in some cell types, including dendritic cells, phagocytes, endothelial cells, and thymic epithelial cells, which have a large capacity for antigen presentation. 25,26 The role of HLA-DR expression in normal lip epithelium and in potentially malignant lesions derived from this tissue is not fully known.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…The expression of these molecules in tumor cells may play different roles in the biological behavior of tumors, sometimes triggering an antitumor immune response, leading to apoptosis of neoplastic cells, or eliciting protumoral functions, favoring tumor growth. 11,[22][23][24] The present study demonstrated for the first time a higher HLA-DR expression in LLSCC tumor cells when compared to cases of AC, suggesting a potential Unlike MHC-I molecules, which are expressed in all nucleated cells, the expression of MHC-II proteins is physiologically observed only in some cell types, including dendritic cells, phagocytes, endothelial cells, and thymic epithelial cells, which have a large capacity for antigen presentation. 25,26 The role of HLA-DR expression in normal lip epithelium and in potentially malignant lesions derived from this tissue is not fully known.…”
Section: Discussionmentioning
confidence: 72%
“…While some studies associate the high expression of HLA-DR in solid tumors with favorable outcomes, 4,7 others suggest that the overexpression of this molecule could indicate a worse prognosis. 10,11 In the case of oral SCC, Li, Zhang and Tong, 6 using immunohistochemistry and in situ hybridization, observed a higher HLA-DR expression in primary carcinomas when compared to the healthy oral mucosa (p < 0.05), but they did not find any statistically significant differences in the immunoexpression of this protein between metastatic lesions and primary carcinomas. Horiuchi et al 5 found a statistically significant association between immunoreactivity to HLA-DR in well-differentiated intraoral SCC tumor cells and lower five-year survival rate of patients.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The expression of T cell inhibitory ligands, including programmed death ligand-1 (PD-L1), PD-L2, carcinoembryonic antigen-related adhesion molecule-1 (CEACAM-1), lymph node sinusoidal endothelial cell C-type lectin (LSECtin), and major histocompatibility complex (MHC) class II, on cancer cells also affects the anti-tumor activity of activated CD8 positive T cells such as CTLs. There have been some reports showing evidences regarding the expression levels of these ligands in GC patients [18][19][20].…”
Section: Supplementary Informationmentioning
confidence: 99%
“…It is conceivable that tumor cells could somatically alter these genes in order to avoid antigen presentation synonymous to Type I or II BLS. Interestingly, somatic variants in Type-II BLS genes identified in a subset of gastric cancers were found to be associated with lack of recurrence [19]. To explore BLS genes as a target for somatic disruption of antigen presentation, we investigated four cancer types with high TMB in TCGA (colorectal, melanoma, gastric and uterine).…”
Section: Introductionmentioning
confidence: 99%